2004
DOI: 10.1641/0006-3568(2004)054[1119:fcasom]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Financial Costs and Shortfalls of Managing and Expanding Protected-Area Systems in Developing Countries

Abstract: Underfunding jeopardizes the ability of protected areas to safeguard biodiversity and the benefits that intact nature provides to society. In this article, we evaluate the cost of effectively managing all existing protected areas in developing countries, as well as the cost of expansion into highpriority new areas. We find that recent studies converge on a funding shortfall of $1 billion to $1.7 billion per year to manage all existing areas. The costs of establishing and managing an expanded protected-area sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
233
1
18

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(256 citation statements)
references
References 23 publications
1
233
1
18
Order By: Relevance
“…After published estimates (22,24), we calculate that annual management costs per site in developing countries will likely span four orders of magnitude, from $470 to $3,500,000 (median $220,000). Annual costs for each of three sites in Ecuador, for example, average $36,000 (managed by Fundación Jocotoco; R.R., unpublished data).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After published estimates (22,24), we calculate that annual management costs per site in developing countries will likely span four orders of magnitude, from $470 to $3,500,000 (median $220,000). Annual costs for each of three sites in Ecuador, for example, average $36,000 (managed by Fundación Jocotoco; R.R., unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…Annual costs for each of three sites in Ecuador, for example, average $36,000 (managed by Fundación Jocotoco; R.R., unpublished data). One-time acquisition costs for unprotected sites can be many times their management costs (25) but may often be much lower because protection may be achieved through redesignation of public lands to higher levels of protection or better enforcement of existing designations (24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this approach, we assume that a particular activity has one standard price, within a certain (spatial) context. Nonetheless, previous studies (Balmford et al, 2003;Bruner et al, 2004;Vreugdenhil, 2003) have found that standard price variations can be explained by sizes of protected areas, the population density of a particular country or nearby conservation sites and the income level of countries.…”
Section: Introductionmentioning
confidence: 95%
“…The size of areas may strongly determine unit costs of nature management (e.g. Balmford et al, 2003;Vreugdenhil, 2003;Bruner et al, 2004). Large areas are relatively less costly to manage than small areas.…”
Section: 4mentioning
confidence: 99%